Educación popular en Morelia. La fundación de la Secundaria Popular Carrillo Puerto, 1976-1985 - Armas Madrigal, Erika (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
Starting in the 1960s, there was a popular education movement in Latin America, whose goal was the liberation of the oppressed. It arose as a result of events such as the dictatorships in Argentina and Brazil and after the Cuban Revolution. Authors like Paulo Freire contributed to the systematization of popular education experiences. In Mexico, these experiences also occurred with political-pedagogical projects carried out by university students from student movements, who fought for popular, critical, and scientific education. In the case of Michoacán, the students also had the influence of Cardenismo's socialist education. The context of Morelia during the 1970s, in which secondary education was inaccessible to the most humble sectors of the population, led the Nicolaitan students to found secondary schools on the street, from which the Popular High School was born, with the support of merchants, workers, peasants, fathers and mothers of rejected students. The Popular High School was born in 1976 as a space for children of workers and peasants, linked to the Universidad Michoacana. The basic education institution embodied the ideals that the Nicolaitans sought for their university, such as autonomy and student participation in decision-making. Other characteristics of the popular project were the implementation of workshops, its self-organization and self-sustainability.

A partir de la década de 1960 se dio el movimiento de educación popular en América Latina, que tuvo como fin la liberación de los oprimidos. Surgió a raíz de acontecimientos como las dictaduras en Argentina y Brasil y luego de la Revolución Cubana. Autores como Paulo Freire contribuyeron con la sistematización de experiencias de educación popular. En México también se dieron estas experiencias con proyectos político pedagógicos llevados a cabo por universitarios de los movimientos estudiantiles, que lucharon por una educación popular, crítica y científica. En el caso de Michoacán, los estudiantes tenían también la influencia de la educación socialista del cardenismo. El contexto de Morelia durante la década de los setenta, en que fue inaccesible la educación secundaria para los sectores más humildes de la población, llevó a los estudiantes nicolaitas a la fundación de secundarias de la calle, de donde nació la Secundaria Popular, con el apoyo de comerciantes, obreros, campesinos, papás y mamás de estudiantes rechazados. La Secundaria Popular nació en 1976 como un espacio para hijos de obreros y campesinos, ligado a la Universidad Michoacana. En la institución de educación básica se plasmaron los ideales que los nicolaitas buscaron para su universidad, como la autonomía y la participación estudiantil en la toma de decisiones. Otras características del proyecto popular fueron la implementación de talleres, su autoorganización y el autosostenimiento.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2023-0872; Historia de México; Movimiento estudiantil; Educación alternativa; Protesta; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16643